Penerapan Sistem Informasi Akuntansi Penggajian Pegawai ASN dan Non ASN Pada Badan Pengelolaan Keuangan dan Pendapatan Daerah Kabupaten Buleleng - Ni Komang Erina Liliani; I Gede Agus Pertama Yudantara (Universitas Pendidikan Ganesha, 2022)
This study aims to find out about how to implement accounting information systems for ASN and non-ASN employees at the Buleleng Regency Financial and Revenue Management Agency. The subject in this study is the Regional Finance and Revenue Management Agency of Buleleng Regency, and the object of this research is the Application of the ASN and Non ASN Employee Payroll Accounting Information System at the Buleleng Regency Financial and Revenue Management Agency. The data collection method used in this study is the observation method, interview method, and documentation method. Qualitative descriptive data analysis techniques were used in this study to describe the data obtained in the study. This study shows how the payroll accounting information system used in the Finance and Revenue Management Agency of Buleleng Regency.